Lower Face-Lift with Extensive Neck Recontouring - Langsdon, Phillip; Shires, Courtney; Gerth, David (Facial Plastic Surgery, 2012)
Difficult anatomy and advanced aging continue to pose a challenge to the face-lift surgeon. We present a thorough analysis of the patient with respect to relevant vascular anatomy, as well as our techniques used to address advanced cases, including compartment communication and submental suspension platysmaplasty.
Keywords: face-lift; angiosome; platysmaplasty; cervicoplasty